2006
DOI: 10.1111/j.1365-2885.2006.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the relationship between serum and milk residue disposition of ceftriaxone in lactating ewes

Abstract: The present study was planned to investigate the serum disposition kinetics and the pattern of ceftriaxone elimination in milk and urine of lactating ewes (n = 6) following i.v. and i.m. administration. A crossover study was carried out in two phases separated by 15 days. Ceftriaxone was administered at a dosage of 10 mg/kg b.w. in all animals. Serum, milk and urine samples were collected between 0 and 72 h and a modified agar diffusion bioassay method was used to determine the percentage of protein binding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
4
15
0
Order By: Relevance
“…, 1990). A previous report characterizing the pharmacokinetics of ceftriaxone in lactating ewes found that the kinetic parameters calculated for the lactating animals were similar to those recorded in a previous report for nonlactating sheep (Goudah et al. , 2006).…”
Section: Discussionsupporting
confidence: 83%
“…, 1990). A previous report characterizing the pharmacokinetics of ceftriaxone in lactating ewes found that the kinetic parameters calculated for the lactating animals were similar to those recorded in a previous report for nonlactating sheep (Goudah et al. , 2006).…”
Section: Discussionsupporting
confidence: 83%
“…The calculated value for apparent volume of distribution of ceftriaxone (0.5±0.19 L.kg −1 ) in healthy cows indicated moderate distribution of the drug. In agreement to the present results, lower values of Vd area have been reported for ceftriaxone in ewes (0.28 L.kg −1 ), camel (0.32 L.kg −1 ) and goats (0.28-0.58 L.kg −1 ) after intravenous administration (Goudah et al 2006;Sar et al 2006;Goudah 2008;Tiwari et al 2009). However, large Vd area has also been Cp 0 = plasma drug concentration at time zero of intravenous dosing; α 1 and α 2 = distribution rate constants from central to peripheral compartments; β = elimination rate constant; t 1/2 α 1 and t 1/2 α 2 = distribution half lives of the two distribution phases; t 1/2 β = elimination half life; K 12 , K 13 , K 21 and K 31 = rate constants of drug transfer from central to peripheral compartments and vice-versa; AUC = area under the plasmaconcentration time curve; AUMC = area under the first moment of plasma-concentration time curve; Vd (area) = apparent volume of distribution; Cl B = total body clearance of drug; K el = rate constant for elimination of drug from central compartment; MRT = mean residence time; P/C = ratio of drug present in peripheral to central compartment reported for ceftriaxone in calves (1.91 L.kg −1 ) and buffalo calves (1.4 L.kg −1 ) following intravenous administration (Johal and Srivastava 1999;Dardi et al 2004).…”
Section: Discussionsupporting
confidence: 94%
“…Lower value of AUC of ceftriaxone in endometritic cows (37.0±17.1 μg.ml −1 .h) in comparison to its corresponding value in healthy cows reflected a smaller area covered under drug concentration during endometritis in animals. The short elimination half-life of ceftriaxone in healthy cows (1.02±0.07 h) was comparable to the t ½β of 1.5 h in goats, 1.75 h in ewes, 1.27 h in buffalo calves, 0.81 h in mares and 83.8 min in neonate calves (Soback and Ziv 1988;Gardner and Aucoin 1994;Goudah et al 2006;Gohil et al 2009;Tiwari et al 2009), however it was shorter than the t ½β of 4.39± 0.63 h in calves and 2.57 h in camels (Johal and Srivastava 1999;Goudah 2008) after intravenous injection of ceftriaxone. The average mean residence time of ceftriaxone in healthy cows observed in the present study was 1.55±0.25 h. Similar low values have been reported for the MRT of ceftriaxone in goats (1.01 h), buffalo calves (1.34 h), ewes (1.93 h) and neonatal calves (1.57 h) following its intravenous dosing (Soback and Ziv 1988;Goudah et al 2006;Gohil et al 2009;Tiwari et al 2009).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations